2014
DOI: 10.3813/aaa.918708
|View full text |Cite
|
Sign up to set email alerts
|

Soundscape Reproduction and Synthesis

Abstract: The aims of this work were to investigate (i) whether soundscape perceptual dimensions are correctly reproduced by ambisonic loudspeaker playback, (ii) whether soundscape dimensional analysis is robust to changes of location and from the field to laboratory playback, and (iii) whether a simple soundscape synthesis can be used to interactively design a soundscape. The first two aims were addressed by an experiment which attempted to repeat To investigate the third aim, the ambisonic reproduction was extended to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 9 publications
(16 reference statements)
5
32
0
Order By: Relevance
“…Brown, Kang, & Gjestland, 2011;Brown, 2012). Davies, Bruce and Murphy (2014) reported that when participants were asked to design a soundscape in a laboratory environment, the designed soundscapes seemed to be based more on the participants' expectations of typical urban soundscapes than on their own preferences for individual sounds. Thus, it seems reasonable to investigate what sounds are heard in a place and how appropriate they are.…”
Section: Appropriatenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown, Kang, & Gjestland, 2011;Brown, 2012). Davies, Bruce and Murphy (2014) reported that when participants were asked to design a soundscape in a laboratory environment, the designed soundscapes seemed to be based more on the participants' expectations of typical urban soundscapes than on their own preferences for individual sounds. Thus, it seems reasonable to investigate what sounds are heard in a place and how appropriate they are.…”
Section: Appropriatenessmentioning
confidence: 99%
“…Guastavino et al (2005) raised the issue of ecological validity when reproducing acoustic environments, questioning whether the perception of a reproduced acoustic environment is the same or different from what might be expected in situ. Davies et al (2014) recently published promising results, concluding that acoustic environments recorded and reproduced by Ambisonics may be ecologically valid for soundscape appraisal.…”
Section: Collecting Soundscape Datamentioning
confidence: 99%
“…Ambisonic reproduction is flexible to be applied in any sound playback configurations, which makes it very attractive to be used in a wide variety of applications [67]. Davis et al [21] used the first order ambisonic microphones to record the background ambient soundscape and used a monophonic microphone to record the foreground sounds separately. The soundscape synthesis was carried out using a simulation tool.…”
Section: Physical Reconstruction Of Soundmentioning
confidence: 99%
“…Perceptual accuracy is the basis of auralization [18], and is largely influenced by the spatial properties of sounds such as source distance, source location, and reverberation [19,20]. Several laboratory experiments on ecological validation of the reproduction systems have been conducted based on the psycholinguistic measure, such as semantic differential method [16,21,22]. Those studies compared the subjective responses of verbal descriptors on soundscape among in situ acoustic environments and the reproduced acoustic environments created by different techniques in laboratory conditions to explore the ecological validity of reproduction systems.…”
Section: Introductionmentioning
confidence: 99%
“…A key issue is how to condense an urban sound recording into a shorter format whilst retaining ecological validity. Methods for this have included selection of small clips at random [15] or manually arranging a acoustic scene "composition" in order to "create a balanced impression" [19]-essentially condensing the acoustic scene by ear. Whilst manual composition of a stimulus is undoubtably more robust than presentation of a random short clip that may or may not be representative of the acoustic scene as a whole, it is not an optimal process.…”
Section: Introductionmentioning
confidence: 99%